Modern technology and the international copyright protection system: keeping a barrier between the freedom od knowledge and the freedom of privacy - Козін, Олександр Борисович; Козин, Александр Борисович; Kozin, Oleksandr B.; Задерейко, Олександр Владиславович; Задерейко, Александр Владиславович; Zadereyko, Oleksandr V.; Бегматова, Ф. М.; Behmatova, F. M. (My University, 2014)
This article focuses on the international copyright protection system and how it interacts with intellectual property. The unresolved problems of modern jurisprudence, the question of a fair balance between the right to freedom of information and protection of intellectual property rights is one of the most pressing issues in international policy. This is why it is such a big issue in the scientific community. It talks about keeping a steady balance between freedom of privacy and freedom of information. Internet, allowing to create and share information from anywhere in the world. It has radically changed relations, making material the product of its creator, publisher, and distributor. An effective system of intellectual property protection helps to create a civilized environment where entrepreneurs, and consumers would be protected from unauthorized use of intellectual property. Balancing the interests of rights holders and the rest of society is recognized as a fundamental aspect in the field of intellectual property. This meeting was set up to formally introduce Ukrainian judges to copyright information and to produce recommendations for future cases. Modern jurisprudence's unresolved problems are also discussed in relation to Ukraine and the changes that are being made to make these copyright laws to be more effective.

Эта статья посвящена взаимодействию международной системы защиты авторских прав с интеллектуальной собственностью. Проблема сохранения устойчивого баланса между информационной свободой и её должной защитой. Вопросы мировой и, в частности, украинской юриспруденции в контексте современности.

Ця стаття присвячена взаємодії міжнародної системи захисту авторських прав з інтелектуальною власністю. Проблема збереження стійкого балансу між інформаційною свободою і її належним захистом. Питання світової і, зокрема, української юриспруденції в контексті сучасності.
Kozin A. B. Modern technology and the international copyright protection system: keeping a barrier between the freedom od knowledge and the freedom of privacy / A. B. Kozin, A. V. Zadereiko, F. M. Behmatova // Альманах міжнародного права. Вип. 6. - Одеса, 2014. - С. 127-132.
Keywords: copyright protection system; modern jurisprudence; intellectual property rights; digital rights management systems; система защиты авторских прав; современная юриспруденция; права интеллектуальной собственности; цифровых систем правового регулирования; система захисту авторських прав; сучасна юриспруденція; права інтелектуальної власності; цифрові системи правового регулювання